Traumatic Brain Injury Clinical Characteristics and Outcomes - Badenes, Rafael (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
As many of you already know, traumatic brain injury (TBI) is a growing public health problem of substantial proportions. More than 50 million TBIs occur internationally each year. Across all ages, TBI represents 30-40% of all injury-related deaths, and neurological injury is projected to remain the most important cause of disability from neurological disease until 2030. Severe TBI has a high mortality rate, estimated at 30-40% in observational studies on unselected populations. Survivors experience a substantial burden of physical, psychiatric, emotional, and cognitive disabilities, which disrupt the lives of individuals and their families, and impose huge costs on society. Wide variations in the clinical manifestations of TBI are attributable to the complexity of the brain and to the pattern and extent of damage. Over the past few years, a number of multicenter studies on the topic have emerged, helping to provide a better understanding of the condition. However, it is also clear that much remains to be learned.